Transcultural Memories and Transmission: The Case of Ying Chen’s 'La lenteur des montagnes' - Gabrielle Parker (Modern Languages Open)
As a plurilingual, nomadic writer shaped by and immersed in different cultures, Ying Chen rebels against the facile expectation of the transnational writer to be “a bridge” between cultures and calls for a degree of reciprocity in the nurturing of exchanges across cultures and contexts. Yet, as this article argues, Chen’s preoccupation with transmission and her transcultural perspectives on transcultural memories are evident in her literary practice. Although for the main part her creative writing has presented a female character suspended in an in-between space and distanciated from specific cultural boundaries, Chen’s recent fiction is more explicit in articulating transnational/transcultural constructions of identity in characters who have experienced cultural and linguistic dislocation. Her twin concerns are clearer still in her essays, more particularly in La lenteur des montagnes (2014), which will be the main focus of our study of the author’s exploration of the value of transcultural creativity and the notion transmission.